Pengaruh Variasi Kadar Pengisi Laktosa dan Manitol terhadap Sifat Fisik Granul sebagai Produk Antara Tablet Effervescent Ekstrak Daun Senna (Cassia acutifolia) - Mayu Rahmayanti (Journal of Islamic Pharmacy, 2021)
Senna leaf (Cassia acutifolia) is a plant that is widely known by the public to treat constipation. Senna leaf products have weaknesses in the form of an unpleasant aroma and taste and the use of inappropriate doses. This study aims to determine the effect of variations in the levels of lactose and mannitol as filler on the physical properties of the effervescent granules of senna leaf extract. Effervescent granules were made using the melting method with a ratio of lactose and mannitol 25% : 75%, 50% : 50%, and 75% : 25%, while the extraction method for senna leaves used the infundation method with distilled water as a solvent. The effervescent granules obtained were tested for flow time, angle of repose, setting and moisture content. The data obtained were analyzed by theoretical approach and statistical test using analysis of variance (ANOVA) with 95% confidence level. The results showed that the use of variations in the filler levels of lactose and mannitol with groups of 25% : 75%, 50% : 50%, and 75% : 25%,  could affect the moisture content and angle of repose of the granules but had no effect on the compressibility and flow time of the granules. Keywords : Cassia acutifolia, sennoside, laxative, effervescent granules, mannitol, lactose